How does land use change affect the methane emission of soil in the Eastern Amazon? - Lage Filho, Nauara Moura; Cardoso, Abmael da Silva; Azevedo, Jorge Cardoso de; Macedo, Vitor Hugo Maués; Domingues, Felipe Nogueira; Faturi, Cristian; Silva, Thiago Carvalho da; Ruggieri, Ana Cláudia [UNESP]; Reis, Ricardo Andrade [UNESP]; do Rêgo, Aníbal Coutinho (Frontiers, 2023)
Methane emissions (CH4) from the soil increase according to changes made in forest soils and adverse edaphoclimatic factors. Soil temperature and nutrients will impact the activity of microorganisms, depending on land use. The objective of this study was to evaluate the impacts of land use, temperature, and nitrogen application on CH4 emissions from soils within the Amazon region. Three experiments were conducted in a completely randomized design. Each experiment consisted of five replicates to measure CH4 emissions. The variables examined in these experiments were: 1) three distinct land uses (forest, pasture, or agriculture; 2) soil temperatures (25, 30, 35, or 40°C); and 3) input of nitrogen to the soil (0, 90, 180, or 270 kg of N ha−1). In this study, the highest emissions occurred in pasture soils, with values of 470 μg of CH4 g−1 of dry soil, while forest and agricultural soils suffer the effects of CH4 oxidation. Temperature is a factor that contributes to CH4 emissions, and temperatures above 30°C tended to reduce gas emissions in the systems studied, since the highest emission was observed in pasture soil kept at 25°C (∼1,130 μg of CH4 g−1 of dry soil). Nitrogen fertilization in pasture soils reduces CH4 emitted nearly 140% as the dose increased. As a result, the pasture soils tended to emit higher concentrations of CH4 into the atmosphere. However, reducing these emissions from the pasture management employed is possible.
Keywords: arc of deforestation of the Amazon; CH4 drivers; land use change; nitrogen; temperature